Peculiarities of Epidemiological Situation on the West Nile Fever in the Russian Federation in 2020 and Forecast for Its Development in 2021 - E. V. Putintseva; S. K. Udovichenko; N. V. Boroday; D. N. Nikitin; A. А. Baturin; E. V. Molchanova; I. M. Shpak; V. K. Fomina; A. V. Nesgovorova; A. S. Antonov; D. R. Prilepskaya; D. V. Viktorov; et al. (Проблемы особо опасных инфекций, 2021)
The paper presents an analysis of West Nile Fever incidence in the Russian Federation in 2020, summarizes the results and identifies problematic issues of the pathogen monitoring. Manifestations of West Nile Fever in 2020 were characterized by a low incidence rate (10 times lower than the average long-term value) with sporadic cases registration in the endemic areas of the Southern (9 cases) and Central (1 case) Federal Districts. A discrepancy between the morbidity structure (distribution by age, sex, social status) and the trends that have developed in Russia in recent years is shown. The analysis of officially recorded cases doesn’t characterize the epidemic process of West Nile fever in Russia during 2020-season as a whole. The generalized results of monitoring of the West Nile virus circulation in environmental objects in 2020 indicate a decrease in the effectiveness of its implementation and a low detectability of pathogen markers. A decrease in the volume of diagnostic studies for the active detection of patients with West Nile fever in the epidemic season (5.7 times lower compared to 2019), as well as serological screening of healthy population samples (1.6 times) has been established. The results of a molecular-genetic study of the pathogen showed that lineage 2 of the pathogen was circulating in the European part of Russia. The circulation of the lineage 4 of the virus in the enzootic cycle in the Republic of Kalmykia was found out. The genome sequences of 11 West Nile virus isolates allocated in 2019 and 2020 were obtained. Phylogenetic analysis revealed that all isolates allocated in the Volgograd Region and isolates from the Rostov and Astrakhan regions belong to the Volgograd clade of the lineage 2 of the West Nile virus. Based on the assessment of abiotic and biotic factors, possible local increases in the incidence of West Nile fever in 2021 in the regions of the Southern and North Caucasian Federal Districts and in the south of Western Siberia have been substantiated.